(untitled) (Quantum Frontiers Journal P-ISSN 3117-6070 and E-ISSN 3117-6089, 2024)
Claims of quantum advantage for combinatorial optimisation require rigorous comparison against state-of-the-art classical algorithms under controlled experimental conditions – yet the quantum computing literature frequently benchmarks quantum methods against weak classical baselines such as greedy heuristics or random search, inflating apparent quantum advantage. This paper presents the Quantum-Classical Combinatorial Benchmark (QCCB), a rigorous comparative study of quantum optimisation algorithms (QAOA, VQE-QUBO, hybrid QA) against nine state-of-the-art classical algorithms (Goemans-Williamson SDP, simulated annealing, tabu search, CPLEX branch-and-bound, OR-Tools CP-SAT, Gurobi MIP, Benders decomposition, extremal optimisation, and population-based iterated local search) across six canonical combinatorial problem classes (MaxCut, Vertex Cover, Graph Colouring, Knapsack, Set Cover, and Weighted Max-SAT) at problem sizes n = 12 to n = 256. QCCB finds that no quantum algorithm consistently outperforms all classical baselines across all problem classes at current NISQ scale. QAOA with QOAS adaptive depth (Bianchi, 2024) outperforms all nine classical algorithms on MaxCut at n = 48 (approximation ratio 0.924 vs. GW 0.878). However, classical Gurobi MIP and CPLEX solve MaxCut exactly for n up to n = 84 within the same time budget, eliminating the QAOA advantage at moderate scale. QCCB provides nuanced guidance on problem classes, instance sizes, and time budgets where quantum algorithms offer genuine near-term advantage.